1976
DOI: 10.1080/00219266.1976.9654076
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to restructuring school biology

Abstract: Two structuring principles are discussed which both drop the old 'systematic' (taxonomic as well as subdiscipline-bound) way of structuring biological subject matter. They lead to a biology curriculum with great social and inter-disciplinary impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Cooperation between different subject teachers is not usual. Kattmann and Schaefer (1976) have already reported that biology instruction in the Sekund arstufe I in West Germany is increasingly moving away from the use of taxonomy as the structuring principle. On the contrary, attempts have been made to teach biology as separate sub-disciplines.…”
Section: Introductionmentioning
confidence: 97%
“…Cooperation between different subject teachers is not usual. Kattmann and Schaefer (1976) have already reported that biology instruction in the Sekund arstufe I in West Germany is increasingly moving away from the use of taxonomy as the structuring principle. On the contrary, attempts have been made to teach biology as separate sub-disciplines.…”
Section: Introductionmentioning
confidence: 97%